Virtual hairstyle studio (V-Hair) / Lee Ean Har - Lee , Ean Har (2003)
Virtual Hairstyle Studio is an interactive hairstyle simulation program for the saloons and customers. Virtual Hairstyle Studio is also named as V-Hair, Virtual HairStyle Studio is developed using Visual Basic 6.0, Microsoft Access 2000, Adobe Photoshop 6.0 and Macromedia Flash MX. We would often listen that "I wonder how would I am going to be the haircut or hair colour". Normally it is difficult to make up our mind to select which haircut or hair dyeing colour whenever we attempt to change new image. Thus, V-Hair is aimed to overcome the uncertainty by providing an interesting visualization to saloon's customers. v-Hair is absolutely risk-free for customers to try on any hairstyle anytime visually. In addition, V-Hair also is able to tell customers 'what face shape suites what hairstyle' in the perfect way. Tips for solutions to hair's problem and hair care hints can be found in V-Hair as well. Since there is not many similar systems available in the local market, Virtual Hairstyle Studio is undoubtedly will provide an attractive service to any saloons which adopt this system.